2018
DOI: 10.1038/s41598-018-31863-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait Loci and Candidate Genes for Maize Starch Granule Size through Association Mapping

Abstract: Starch is an important nutrient component of maize kernels, and starch granule size largely determines kernel waxiness, viscosity, and other physiochemical and processing properties. To explore the genetic basis of maize starch granule size, 266 tropical, subtropical, and temperate inbred lines were subjected to genome-wide association analyses with an array of 56,110 random single nucleotide polymorphisms (SNPs). In the present panel, the kernel starch granule size ranged from 7–15.8 µm long and 6.8–14.3 µm w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
8
1
Order By: Relevance
“…Considering the association panel size and looking at the background noise in the obtained Manhattan plots, this threshold of −log 10 ( P -value) = 4 seemed acceptable to prevent missing potentially interesting regions, at the cost of using a more conservative kind of correction such as Bonferroni. Examples of other maize studies with similar association panel sizes and the number of markers using the same threshold are found in the works reported by Liu et al , For the SNPs significantly associated with the 15 volatiles variation [log 10 ( P -value) > 4], the effect of the minor frequency SNP variant, reported when compared to the most frequent allele reference, was also calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the association panel size and looking at the background noise in the obtained Manhattan plots, this threshold of −log 10 ( P -value) = 4 seemed acceptable to prevent missing potentially interesting regions, at the cost of using a more conservative kind of correction such as Bonferroni. Examples of other maize studies with similar association panel sizes and the number of markers using the same threshold are found in the works reported by Liu et al , For the SNPs significantly associated with the 15 volatiles variation [log 10 ( P -value) > 4], the effect of the minor frequency SNP variant, reported when compared to the most frequent allele reference, was also calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several genome association studies with starch granules size distribution were published for maize (Liu et al, 2018), wheat (Li et al, 2017;Chia et al, 2020) and Japonica rice (Biselli et al, 2019). In the present study, no noticeable SNPs with p-values higher than Bonferroni or FDR levels were found for average values for the "Area", "Feret's diameter", "Minimal Feret's diameter" and "Solidity" traits.…”
Section: Manhattan Plotscontrasting
confidence: 54%
“…Recently, several genome association studies with starch granules size distribution were published for maize ( Liu et al, 2018 ), wheat ( Li et al, 2017 ; Chia et al, 2020 ) and Japonica rice ( Biselli et al, 2019 ). In the present study, no noticeable SNPs with p -values higher than Bonferroni or FDR levels were found for average values for the “Area”, “Feret’s diameter”, “Minimal Feret’s diameter” and “Solidity” traits.…”
Section: Resultsmentioning
confidence: 99%